Towards Iron-Catalysed Suzuki Biaryl Cross-Coupling: Unusual Reactivity of 2-Halobenzyl Halides - Bedford, Robin B.; Gallagher, Timothy; Pye, Dominic R.; Savage, William (Synthesis, 2015)
The reaction of 2-halobenzyl halides with the borate anion Li[(Ph)(t-Bu)Bpin] leads not only to the expected arylation at the benzyl position, but also to some Suzuki biaryl cross-coupling. Preliminary mechanistic investigations hint towards the intermediacy of benzyl iron intermediates that can either: (a) directly cross-couple with the aryl boron reagent to give observed monoarylated species, or (b) undergo oxidative addition of the aryl halide to generate the diarylated species on reaction with the boron-based nucleophile.
Keywords: iron; cross-coupling; aryl; Suzuki reaction; organoborate